NEW METHODS OF INCLINED DRILLING OF OIL AND GAS WELLS: AN IMRAD-STRUCTURED SCIENTIFIC ARTICLE (Web of Technology: Multidimensional Research Journal, 2025)
The growing complexity of global hydrocarbon reservoirs has rendered conventional vertical drilling methods insufficient for accessing structurally heterogeneous and deeply seated formations. New methods of inclined drilling have become essential for effective reservoir penetration, enhanced production, and optimized field development. This paper provides a comprehensive IMRAD-based scientific analysis of the newest inclined drilling technologies, including rotary steerable systems, gyroscopic navigation, real-time geosteering, advanced drilling fluid systems, automated drilling control, and hybrid thermal–mechanical drilling approaches. Through a synthesis of engineering principles, digital innovations, and field performance data, the study demonstrates that modern inclined drilling significantly increases reservoir contact, improves rate of penetration, reduces operational risks, and minimizes environmental footprint. The results highlight how automation, real-time analytics, and adaptive tools have transformed inclined drilling into a predictive, highly efficient process. The integration of digital twin simulations and advanced downhole tools has further strengthened trajectory accuracy and drilling efficiency. This article concludes that new inclined drilling methods will remain a critical technological foundation for future oil and gas extraction as global reservoirs continue to evolve in complexity and depth.